Implementing RIAS Model with SSI Approach to Improve Argumentation Skills: Penerapan Model RIAS dengan Pendekatan SSI untuk Meningkatkan Kemampuan Argumentasi - Ramadhani, Adista Enggar Putri; Ismawati, Riva; Dewantari, Nuryunita (Academia Open, 2026)
General Background: Argumentation skills are crucial in science education but remain underdeveloped due to traditional teacher-centered learning methods. Specific Background: Current science instruction often lacks opportunities for evidence-based reasoning and does not engage students in real-life contextual issues. Knowledge Gap: Although various models exist, there is a lack of research on the integration of structured models like RIAS with real-world issues for improving argumentation skills. Aims: This study aims to assess the effectiveness of the RIAS model, combined with the Socio-Scientific Issues (SSI) approach, in enhancing middle school students' argumentation skills. Results: The findings indicate that the RIAS-SSI model significantly improved students' argumentation skills, with the experimental group showing a substantial increase in their argumentation scores, particularly in the use of evidence and logical reasoning. Novelty: This study is novel in its combination of RIAS and SSI, creating an integrative learning model that systematically enhances students' argumentation through contextual issues. Implications: The results suggest that incorporating RIAS with SSI in science education can foster critical thinking and argumentation skills, aligning with 21st-century educational goals. HIGHLIGHTS Integration of RIAS with SSI significantly improved students' argumentation. The experimental group demonstrated stronger skills in evidence and reasoning. The RIAS-SSI approach offers a systematic and contextual method for science learning KEYWORDS RIAS Model; Socio-Scientific Issues; Argumentation Skills; Science Education; Critical Thinking